2016
DOI: 10.3389/fphys.2016.00433
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin/NFAT Activation-Dependence of Leptin Synthesis and Vascular Growth in Response to Mechanical Stretch

Abstract: Background and Aims: Hypertension and obesity are important risk factors of cardiovascular disease. They are both associated with high leptin levels and have been shown to promote vascular hypertrophy, through the RhoA/ROCK and ERK1/2 phosphorylation. Calcineurin/NFAT activation also induces vascular hypertrophy by upregulating various genes. This study aimed to decipher whether a crosstalk exists between the RhoA/ROCK pathway, Ca2+/calcineurin/NFAT pathway, and ERK1/2 phosphorylation in the process of mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Another report demonstrated that Drp1 is dephosphorylated at Ser 637 by calcineurin to cause its mitochondrial localization and promote mitochondrial fission 50,55 , and the inhibition of calcineurin activity blocks aberrant mitochondrial fission in PD 56 . Importantly, ROCK1 activation is required for calcineurin activation 57 . ROCK1 might indirectly dephosphorylate Drp1 through the induction of calcineurin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another report demonstrated that Drp1 is dephosphorylated at Ser 637 by calcineurin to cause its mitochondrial localization and promote mitochondrial fission 50,55 , and the inhibition of calcineurin activity blocks aberrant mitochondrial fission in PD 56 . Importantly, ROCK1 activation is required for calcineurin activation 57 . ROCK1 might indirectly dephosphorylate Drp1 through the induction of calcineurin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of RASMC started at the same time and the treatment was stopped at the specified time of each condition to minimize the batch effect in the experiment. The selection of these concentrations was based on previous studies [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown a direct involvement of leptin in promoting hypertension-induced vascular hypertrophy [22,23]. Leptin is synthesized by VSMCs in response to forces that mimic hypertension and, in turn, induces VSMC hypertrophy [22][23][24]. This hormone exerts a prohypertrophic effect on VSMCs by activating several signaling pathways and transducers, including the MAPK ERK1/2 [23], the RhoA/ROCK pathway [22,25], and the prohypertrophic transcriptional factors serum response factor (SRF) and GATA-4 [22,25,26].…”
Section: Introductionmentioning
confidence: 99%